Front Cover: Origin of the Isomer Stability of Polymethylated DOTA Chelates Complexed with Ln3+ Ions (Eur. J. Inorg. Chem. 15/2021). Issue 15 (7th April 2021) - Lee, Yong‐Sok; Mou, Zhongyu; Opina, Ana Christina L.; Vasalatiy, Olga
Abstract : The Front Cover shows the isomers of the polymethylated 4S ‐ 4S (5 ) and 4 S ‐4 R (6 )‐M4DOTMA complexed with Lu ions. Each of the pendant arms forms a propeller‐like blade that rotates either in a clockwise (SAP) or counterclockwise (TSAP) direction. The arrow indicates the stable isomer. The presence of the isomers of the Ln complex in solution remains challenging for the analyses of protein dynamics and interactions, as the additional resonances from a Ln tag give rise to unwanted signals. To understand the origin of the stability of one isomer over the other, the structures and energetics of DOTA‐like chelates complexed with Lu ions were investigated with DFT calculations. More information can be found in the Full Paper by Y.‐S. Lee and co‐workers .